Real-world study of adverse events associated with sodium zirconium cyclosilicate based on FDA adverse event reporting system and VigiAccess database - Xiaona Jia; Lei Liu; Pan Wang (PLoS ONE, 2025)
The aim of this study was to investigate frequencies, types, and signals of adverse drug events (ADEs) associated with sodium zirconium cyclosilicate (SZC) used for the treatment of hyperkalemia, in order to inform clinicians of possible safety concerns linked with SZC in real-life usage. ADE reports associated with SZC were collected from both the FAERS and VigiAccess databases. Data extraction from FAERS was performed using OpenVigil 2.1, covering reports from the first quarter of 2004 through the third quarter of 2024. The VigiAccess database was retrieved for reports up to February 5, 2025. The ADEs were standardized and classified by using the preferred term (PT) and the system organ class (SOC) of the Medical Dictionary for Regulatory Activities (MedDRA) (Version 27.0). The reporting odds ratio (ROR) method and the proportional reporting ratio (PRR) method were used to screen positive signals and analyze the characteristics of ADE signals. In this study, 1384 and 1518 ADE reports related to SZC were obtained from the FAERS database and the VigiAccess database, respectively. At the SOC level, the ADEs retrieved in the two databases involved 26 SOCs, and the top 3 SOCs in terms of the number of reported cases were general disorders and administration site conditions, gastrointestinal disorders, and investigations. At the PT level, among the top 30 PTs in terms of the number of reported cases in the two databases, death, cardiac failure, weight increased, blood pressure increased, cardiac failure congestive, cerebrovascular accident, myocardial infarction, pneumonia, dizziness, dysphagia, and dyspnoea were the ADEs with higher number of reported cases not included in the drug instructions. A total of 41 positive signals were obtained after signal screening in FAERS database. Among them, the top 3 PTs in terms of signal strength were blood potassium abnormal (ROR = 180.224[119.925, 270.842]), blood potassium increased (ROR = 98.789[78.835, 123.792]), blood sodium increased (ROR = 35.248[14.624, 84.961]). Signals of cardiac disorders such as cardiac failure chronic, cardiac failure and cardiac failure congestive, signals of gastrointestinal disorders such as ileus and intestinal perforation, and signals of blood sodium increased and hypernatraemia are positive signals that deserve special attention. In this study, the common ADEs associated with SZC were confirmed, and several intriguing novel signals not included in the drug instructions were discovered, which would provide more safety reference data for the clinical use of SZC.